Postcolonial politics and personal laws colonial legal legacies and the Indian state - Williams, Rina Verma (New Delhi ; Oxford : Oxford University Press, 2006)
Placing the contemporary discussion on personal laws in India in historical perspective, this important book views the debate as a critical component of Indian democracy. Balancing the imperatives of multiculturalism, national integration, and gender justice, it affirms that there is a complex continuity between the terms of the debate in the postcolonial Indian state and its colonial counterpart.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Domestic relations (Hindu law) -- History; Inheritance and succession (Hindu law) -- History; Domestic relations (Islamic law) -- India -- History; Inheritance and succession (Islamic law) -- India -- History; India -- Colonization